Pervasive but Neglected: A Perspective on COVID-19-Associated Pulmonary Mold Infections Among Mechanically Ventilated COVID-19 Patients - Ghazanfari, Mona; Arastehfar, Amir; Davoodi, Lotfollah; Yazdani Charati, Jamshid; Moazeni, Maryam; Abastabar, Mahdi; Haghani, Iman; Mirzakhani, Roghayeh; Mayahi, Sabah; Fang, Wenjie; Liao, Wanqing; Nguyen, M. Hong; et al. (Frontiers in Medicine, 2021)
Background: Recent studies from multiple countries have shown a high prevalence of COVID-19 associated pulmonary aspergillosis (CAPA) among severely ill patients. Despite providing valuable insight into the clinical management of CAPA, large-scale prospective studies are limited. Here we report on one of the largest multicenter epidemiological studies to explore the clinical features and prevalence of COVID-19 associated pulmonary mold infections (CAPMI) among mechanically ventilated patients. Methods: Bronchoalveolar lavage (BAL) and serum samples were collected for culture, galactomannan, and beta-D-glucan testing. Patients were classified as probable CAPMI based on the presence of host factors, radiological findings and mycological criteria. Results: During the study period, 302 COVID-19 patients were admitted to ICUs, among whom 105 were mechanically ventilated for ≥4 days. Probable CAPMI was observed among 38% of patients (40/105), among whom BAL culture of 29 patients turned positive for molds, while galactomannan testing on BAL (GM index ≥ 1) and serum (GM index >0.5) samples were positive for 60% (24/40) and 37.5% (15/39) of patients, respectively. Aspergillus (22/29; 75.8%) and Fusarium (6/29; 20.6%) constituted 96.5% of the molds isolated. Diaporthe foeniculina was isolated from a COVID-19 patient. None of the patients presented with CAPMI were treated with antifungal drugs. Conclusion: Despite being a prevalent, the absence of appropriate antifungal treatment highlights that CAPMI is a neglected complication among mechanically ventilated COVID-19 patients admitted to intensive care units. CAPMI can be caused by species other than Aspergillus.